Thymic Carcinoma Treated by CyberKnife Stereotactic Body Radiotherapy - Harada, Yuko (Cureus, 2017)
The standard treatment for advanced thymic carcinoma has not yet been established. Most patients have no symptoms until the advanced stage. Radiation therapy has been used for advanced stage cancer, usually in combination with surgery or chemotherapy; however, the survival rates are 30%-50%. We performed hypofractionated stereotactic radiotherapy with CyberKnife (Accuray, Sunnyvale, CA, USA) for 10 cases of advanced thymic cancer. All cases reached at least partial remission (PR) in two months with progression-free irradiated lesions and minimal radiation-related toxicity. It took only seven to 12 days for each therapy that did not require admission. CyberKnife is beneficial for patients even at the terminal stage.